2018
DOI: 10.1016/j.addbeh.2017.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit internalized stigma: Relationship with risky behaviors, psychosocial functioning and healthcare access among people who inject drugs

Abstract: This research highlights the importance of ongoing research into the implications of internalized stigma for PWID. Assessing both explicit and implicit internalized stigma appears to be beneficial as these are related to different health and behavioral outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 50 publications
(33 reference statements)
4
38
0
Order By: Relevance
“…Endorsement of social stigma and internalized stigma were both negatively related to attitudes towards seeking counselling, which are directly related to intentions to seek counselling. Other studies have reported that the relationship between social stigma and intentions to seek counselling were mediated by internalized stigma, suggesting that those who internalize social stigma are less likely to intend to seek treatment compared to those who do not internalize social stigma von Hippel et al, 2018). As such, both forms of stigma can influence attitudes and have important implications for help-seeking behaviours (Bathje & Pryor, 2011;Corrigan, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Endorsement of social stigma and internalized stigma were both negatively related to attitudes towards seeking counselling, which are directly related to intentions to seek counselling. Other studies have reported that the relationship between social stigma and intentions to seek counselling were mediated by internalized stigma, suggesting that those who internalize social stigma are less likely to intend to seek treatment compared to those who do not internalize social stigma von Hippel et al, 2018). As such, both forms of stigma can influence attitudes and have important implications for help-seeking behaviours (Bathje & Pryor, 2011;Corrigan, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internalized stigma is related to several negative outcomes for marginalized groups, such as increased rates of depression and lower rates of help-seeking behaviour (von Hippel, Brener, & Horwitz, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The experience of stigma can lead to an internalisation of negative views of self as not worthy, less capable, less deserving and at fault. 19 People who use TAOD are a stigmatised group. TAOD use, when seen as a personal choice, suggests self-induced adverse outcomes.…”
Section: Stigma and People Who Use Taodmentioning
confidence: 99%
“…Whether a person anticipates, perceives or experiences stigma and discrimination, this can result in harmful effects on their quality of life, relationships and healthcare utilisation 20,21 . Common adverse outcomes include stress, shame, depression, isolation, maladaptive coping, poor emotional regulation and increased risk taking 22–26 . Stigmatised individuals are also less likely to disclose health conditions (in both healthcare and interpersonal contexts), more likely to avoid healthcare consultations, and less likely to adhere to treatment, thereby reducing treatment effectiveness 26–29 .…”
Section: Stigmamentioning
confidence: 99%
“…Common adverse outcomes include stress, shame, depression, isolation, maladaptive coping, poor emotional regulation and increased risk taking 22–26 . Stigmatised individuals are also less likely to disclose health conditions (in both healthcare and interpersonal contexts), more likely to avoid healthcare consultations, and less likely to adhere to treatment, thereby reducing treatment effectiveness 26–29 . In addition, some healthcare workers may hold negative attitudes towards stigmatised client groups, resulting in discriminatory practices, e.g.…”
Section: Stigmamentioning
confidence: 99%